The Concept of Ta'dib According To Syed Muhammad Naquib Al-Attas and Its Relevance to Contemporary Islamic Education - Samhudi, Samhudi; Idris, Saifullah; M Daud, Al Husaini (IAIN KENDARI, 2025)
This study examines the concept of ta'dib according to Syed Muhammad Naquib al-Attas and its relevance in contemporary Islamic education, with reference to his work The Concept of Education in Islam: A Framework for an Islamic Philosophy of Education. Al-Attas defines ta'dib as the process of internalizing manners, which includes the cultivation of knowledge, moral discipline, and awareness of intellectual and spiritual responsibilities in the proper order of life. This study also examines how the concept of ta'dib can be implemented in modern Islamic education systems and the challenges faced in realizing it. Through a qualitative approach based on literature study, this study finds that the concept of ta'dib according to Al-Attas plays an important role in shaping individuals who not only have intellectual intelligence, but are also civilized, moral, and have an awareness of the true purpose of life. The implementation of ta'dib in modern Islamic education can be done through curriculum reconstruction based on the integration of knowledge and spiritual values, the creation of an educational environment that instills manners as a main principle, and the optimization of the role of educators as role models. However, in practice, the application of ta'dib faces various challenges, such as the secularization of education that separates knowledge from Islamic values, the ambiguity of educational goals that focus more on pragmatic aspects, and a lack of comprehensive understanding of the concept of ta'dib among educators and policymakers. Therefore, the concept of ta'dib is a strategic step in building an Islamic education system that is oriented towards a balance between intellectual intelligence, character building, and spiritual awareness as envisioned.